Kajian Terhadap Ayat-Ayat I'jāz ‘Ilmiy Dalam Surah Al-Ra‘D - Karimah Binti Mat Zin; Imam Fauji; Sharifah Norshah Bani Binti Syed Bidin (Halaqa: Islamic Education Journal, 2018)
This article discusses one of the most important scientific disciplines in the Ulum al-Qurān namely i'jāz al-Qurān. Al-Qurān the book of Allah SWT which is the greatest and eternal miracle to the prophet Muhammad SAW. al-Qurān is the light of rabbani and divine revelation which gives guidance and guidance to all humans. He is a miracle of ruhiyyah akliyyah not hissiyyah. Allah has specified al-Qurān as an eternal miracle of reason throughout the ages so that it becomes the material for thought of scholars and scientists. Hopefully with this study humans can be enlightened rather than light, get benefits rather than clues to face the days ahead. In al-Qurān there are many forms of i'jāz including al-bayāniy, al-tashrī'iy, al-ghaibiy and al-'ilmiy. In this case the reviewers will focus the study of the miracles of al-Qurān from the point of i'jāz 'ilmiy in the surah al-Ra'd. This study refers to the qualitative method of inquiry, namely the analysis of the texts of the verses of al-Qurān surah al-Ra'd based on the books of muktabar interpretation. Apart from that modern science findings by scholars related were analyzed. The objective of the study is to explain the concept of i'jāz 'ilmiy.